The Role of SFRP1 Expression in Human Breast Cancer. - Li, Yilun. (Tufts Archival Research Center, 2005)
Numerous reports in the literature and data from the Yee laboratory suggest that decreased soluble frizzled-related protein 1 (SFRP1) levels are associated with elevated WNT signaling and poor outcome in breast cancer patients. Therefore, we examined whether SFRP1 expression levels provide a useful diagnostic tool to improve clinical outcomes in human breast cancer. The prognostic value of SFRP1 expression was determined by performing the Kaplan- Meier survival analyses on relapse-free survival (RFS) and overall survival (OS) in five different microarray databases available from the public domain. In addition, in order to determine whether SFRP1 expression predicts clinical outcomes in combination with other reputable prognostic and predictive markers, the expression levels of SFRP1 in combination with the levels of estrogen receptor (ER), progesterone receptor (PR), and EGFR receptor 2 (HER2), in the triple-negative breast cancer (TNBC) subtype, and in the basal/luminal subtypes were examined with parametric and non-parametric T-tests to determine which combinations may help improve clinical predictions. The basal/luminal subtypes were determined via clustergram created from expression profiles of six genes in each datasets. Finally, the prognostic values of SFRP1 expression in combination with basal and luminal subtypes were compared to the prognostic values of basal and luminal subtypes alone to determine whether SFRP1 can improve clinical prediction. Our results have shown that SFRP1 cannot predict the probability of RFS or OS either alone or in combination with the basal/luminal subtypes. However, despite having little success as using SFRP1 expression as a prognostic marker, we showed that in contrast to past assumptions, SFRP1 was overexpressed in ER-underexpressed, non-HER2 overexpressed, TNBC and basal-like breast cancers. These results suggest the potential limitations of SFRP1 and SFRP1 mimentics as therapeutic treatments for breast cancers and called for a need to better understand the role of SFRP1 in breast cancer, especially in the basal-like subtype.